2014
DOI: 10.4103/0974-8237.139201
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic study of the occipital condyle and its surgical implications in transcondylar approach

Abstract: Background:Craniovertebral surgeries require the anatomical knowledge of craniovertebral junction. The human occipital condyle (OC) is unique bony structure connecting the cranium and the vertebral column. A lateral approach like transcondylar approach (TA) requires understanding of the relationships between the OC, jugular tubercle, and hypoglossal canal. Hence, the aim of the present study was to analyze the morphological variations in OCs of dry adult human skull.Materials and Methods:The study was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 22 publications
(53 reference statements)
6
38
4
Order By: Relevance
“…To our view, the sample size is the major factor that influences Parvindokht et al [28] findings. Side symmetry of the OCs thickness and higher values were detected in our sample in males (right, 10.13 ± 1.53 mm and left side, 10.17 ± 1.38 mm) and females (right, 10.09 ± 1.66 mm and left side, 9.88 ± ± 1.51 mm) in contrast to findings of Kalthur et al [14] who found side asymmetry among genders calculating OCs thickness in males (right, 10.4 ± 2.0 mm and left side, 9.9 ± 1.4 mm) and females (right, 9.5 ± 2.0 mm and left side, 8.6 ± 1.4 mm).…”
Section: Discussioncontrasting
confidence: 99%
“…To our view, the sample size is the major factor that influences Parvindokht et al [28] findings. Side symmetry of the OCs thickness and higher values were detected in our sample in males (right, 10.13 ± 1.53 mm and left side, 10.17 ± 1.38 mm) and females (right, 10.09 ± 1.66 mm and left side, 9.88 ± ± 1.51 mm) in contrast to findings of Kalthur et al [14] who found side asymmetry among genders calculating OCs thickness in males (right, 10.4 ± 2.0 mm and left side, 9.9 ± 1.4 mm) and females (right, 9.5 ± 2.0 mm and left side, 8.6 ± 1.4 mm).…”
Section: Discussioncontrasting
confidence: 99%
“…Although some studies suggested these did not have a correlation with the sagittal and the transverse diameter of the FM [43], other studies reported a sexual dimorphism for FM dimensions with all parameters being significantly higher in males [44]. Kamath et al [45] found sex predictability (higher values in males) for FM area (70.3%), followed by sagittal diameter (69.6%), and least for transverse diameter (66.4%), similar to the study of Uthman et al [46] for FM area and Raghavendra Babu et al [47] with higher predictability for FM area and sagittal diameter compared to transverse diameter [9]. Rai et al [48] found OC and FM dimensions higher in males compared to females No stastistically significant difference was found in adults for different age groups for the OC [49] and FM [50].…”
Section: Far Lateral Approachsupporting
confidence: 69%
“…and intrinsic lesions [9]. Occipitocervical synostosis is one of the most frequent osseous anomalies of the CVJ and may compress the brainstem, vertebral artery and cranial nerves [10].…”
Section: Introductionmentioning
confidence: 99%
“…There are several anatomical studies in the literature reporting the importance of morphometric variations of the occipital condyles (Kumar & Nagar, 2014, Kavitha et al, Natsis et al, Bayat et al, Das et al, Naderi et al, Ozer et al, Kizilkanat et al, Muthukumar et al, Avci et al, 2011, Bozbug˘a et al, 1999, Kalthur et al, 2014, El-Gaidi et al, 2014, Gapert et al, 2009) and radiological studies have also been conducted (Avci et al, Le et al, 2011, Hong et al, 2011, Noble & Smoker, 1996. Knowledge of the topography of different neurovascular structures located around the region of the occipital condyles is highly important with regard to conducting neurosurgical procedures (transcondylar approach) and obtaining good results.…”
Section: Introductionmentioning
confidence: 99%